PIJAT BAYI TERHADAP PERKEMBANGAN BAYI UMUR 6-11 BULAN DI POSYANDU GRAHA MAJAPAHIT KABUPATEN MOJOKERTO - Ika Yuni Susanti; Dyah Siwi Hety (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
The period of growth and development in infants is a golden period and a critical period for a person occurs at about the age of 0-12 months. The aim of the study was to determine the effect of infant massage on the development of infants aged 6-11 months at Posyandu Graha Majapahit, Mojokerto Regency.The research uses the Pre-Experiment Design type, while the One Group Pre Test-Post Test Design design. The study population was infants aged 6-11 months with a total of 40 infants, while the sample size was 35 infants aged 6-11 months using a simple random sampling technique. Test analysis using the Wilcoxon test.Data analysis used statistical tests conducted in a bivariate manner with the results of the Wilcoxson test showing that there was a significant effect of infant massage on the development of infants aged 6-11 months before and after treatment with a p value of 0.025 <Î± (0.05). So it can be concluded that H1 is accepted, which means there is a significant relationship between infant massage 6-11 months and infant development at Posyandu Graha Majapahit, Mojokerto Regency.Families need to provide support to mothers to provide stimulation, especially baby massage to increase optimal development and strengthen attachment (bonding). Baby massage needs to be done regularly and lovingly. There needs to be education and training on how to massage babies properly and correctly by health workers to mothers of babies as well as regular monitoring of developments.